Linear Equation 13

From Homeworkwiki

Jump to: navigation, search

If m = 2 x - 1 and (3 x + 2) / 2 - (7 - 2 m) / 3 = 11 / 3; find x

Solution:

(3 x + 2) / 2 - (7 - 2 m) / 3 = 11 / 3

=> (3 x + 2) / 2 - [7 - 2 (2 x - 1)] / 3 = 11 / 3

=> (3 x + 2) / 2 - (7 - 4 x + 2) / 3 = 11 / 3

=> (3 x + 2) / 2 - (9 - 4 x ) / 3 = 11 / 3

=> [ 3 (3x + 2) - 2 (9 - 4 x) ] / 6 = 11 /3

=> ( 9 x + 6 - 18 + 8 x ) / 6 = 11 / 3

=> 3 (17 x - 12) = 11 × 6

=> 51 x = 66 + 36

=> 51 x = 102

=> x = 102 / 51 = 2

Personal tools
McAfee SECURE sites help keep you safe from identity theft, credit card fraud, spyware, spam, viruses and online scams